Incidencia del sector no petrolero en el crecimiento económico en Ecuador, período 2013-2022 - Acaro Pacheco, Sofia Alejandra (2024)
This research analyzes the economic growth of Ecuador during the period 2013-2022, considering the impact of the non-oil sector. The study is based on quarterly data from the National Survey of Employment, Unemployment and Underemployment (ENEMDU in Spanish) and the Central Bank of Ecuador (BCE in Spanish). The research examines non-oil Gross Value Added (GVA) as the main variable, and its relationship with control variables such as unemployment, total population, household final consumption expenditure, public spending, exports and inflation. A multiple linear regression model with time series is used to explore the relationships between these variables. Through the multiple linear regression model in time series, the aim is to analyze and predict the behavior of a variable over time. This statistical technique is effective when the data is organized chronologically. In this methodology, the aim is to identify a linear relationship between the independent variables and the dependent variable during a time interval. The results indicate that non-oil GVA has a positive relationship with household final consumption expenditure and exports, being significant in our analysis. This study highlights the importance of diversifying the economy and motivating the economic exercise of the non-oil sector. Recommendations include strengthening the non-oil sector and promoting domestic consumption to improve economic stability through policies to support national companies.